2017
DOI: 10.3389/fnmol.2017.00182
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Oxidative Stress, Mitochondrial Dysfunction, Nrf2 Activation and Inflammation in the Hippocampus Accompany Heightened Systemic Inflammation and Oxidative Stress in an Animal Model of Gulf War Illness

Abstract: Memory and mood dysfunction are the key symptoms of Gulf war illness (GWI), a lingering multi-symptom ailment afflicting >200,000 veterans who served in the Persian Gulf War-1. Research probing the source of the disease has demonstrated that concomitant exposures to anti-nerve gas agent pyridostigmine bromide (PB), pesticides, and war-related stress are among the chief causes of GWI. Indeed, exposures to GWI-related chemicals (GWIR-Cs) and mild stress in animal models cause memory and mood impairments alongsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 109 publications
(111 reference statements)
8
65
0
Order By: Relevance
“…Especially, neuroin ammation is one of the most essential factors in the progression of GWI. As previous reports, excessive neuroin ammation presented in veterans suffering from GWI and also observed in animal model of GWI 21,41 . Part of serum proteins associated with in ammation were signi cantly increased in veterans suffering from GWI, including interleukin 6, C-reactive protein, matrix metalloproteinase-9 (MMP-9) and matrix metalloproteinase-2 (MMP-2) 42,43 .…”
Section: Discussionsupporting
confidence: 76%
“…Especially, neuroin ammation is one of the most essential factors in the progression of GWI. As previous reports, excessive neuroin ammation presented in veterans suffering from GWI and also observed in animal model of GWI 21,41 . Part of serum proteins associated with in ammation were signi cantly increased in veterans suffering from GWI, including interleukin 6, C-reactive protein, matrix metalloproteinase-9 (MMP-9) and matrix metalloproteinase-2 (MMP-2) 42,43 .…”
Section: Discussionsupporting
confidence: 76%
“…When the cell is in an oxidative stress condition, active sites of cysteine residues of Keap-1 were oxidized, thereby prevented Keap-1 from bonding with Nrf2. Then, Nrf2 translocates into the nucleus and bonds to ARE including HO-1 and NQO-1, which are the crucial genes in the brain and is activated by Nrf2 to protect against neurons cell injury (Shetty et al, 2017 ). We thus focused on the role of Nrf2 in-depth.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that GWI-related chemicals can cause chronic oxidative stress, mitochondrial dysfunction and ultimately inflammation of certain areas of the brain, in association with elevated oxidative stress and inflammation at the systemic level 9 . Aspects of mood change and memory impairment due to exposure to GWI-related chemicals were also demonstrated in animal models of GWI 7,10 .…”
Section: Introductionmentioning
confidence: 99%